Spirometry reference values in Indigenous Australians: a systematic review. Issue 1 (4th July 2016) - Blake, Tamara L; Chang, Anne B; Petsky, Helen L; Rodwell, Leanne T; Brown, Michael G; Hill, Debra C; Thompson, Bruce; McElrea, Margaret S
Abstract: Objectives: To evaluate published spirometry data for Australian Aboriginal and Torres Strait Islander (Indigenous) peoples to determine (i) whether their ethnicity influenced spirometry results; and (ii) if any reliable spirometry reference values exist for Indigenous Australians. Study design: Systematic review of published and grey literature. Data sources: PubMed and Cochrane Library databases, references of included articles and appropriate grey literature. Last searches were conducted in April 2016. Study selection: We included any study that performed spirometry on healthy Indigenous Australians and compared their results with those from people of European ancestry. Two authors independently screened titles and abstracts and then reviewed potentially relevant full‐text articles for possible inclusion. We used PRISMA systematic review reporting methods to collate data. Data synthesis: Of a possible 125 studies, 18 full‐text articles were reviewed, but only nine fulfilled the inclusion criteria. None specified Torres Strait Islander inclusion. All studies reported lower spirometry values (as much as 30% lower) for Aboriginal people compared with non‐Indigenous people. Five studies developed spirometry reference values for Indigenous Australians; however, none adhered to all participant inclusion and exclusion criteria outlined by the American Thoracic Society and European Respiratory Society. Hence, reported results and subsequent reference values may not be a true representation of spirometry values in healthy Indigenous people. Conclusions: The lower spirometry values reported for Indigenous Australians may be due to study limitations. Furthermore, there are currently no reliable spirometry reference values for Indigenous Australians that adhere to current guidelines. Developing a set of Indigenous Australian reference values will improve the accuracy of test interpretation and aid in the diagnosis of respiratory disease in this population.